Optimizing Social Media and School Websites for Promotional Branding in Indonesian Madrasahs: Achieving Competitive Advantage in the Digital Era - Mohammad Zainul; Farida Yulianti; Periyadi Periyadi; Dedy Dedy; Shalahuddin Shalahuddin; Ainur Rofiq (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
In today’s rapidly evolving technological landscape, transformation in communication, work patterns, and access to information has reshaped how educational institutions present themselves to the public. Effective use of social media and websites can strengthen madrasas' competitive position amid the rapid flow of information and rising expectations for educational quality. This study explores the utilisation of digital platforms—specifically official websites and Instagram—as promotional tools in MAN 1 and MAN 2 Banjarmasin to enhance their institutional advantage. Employing a qualitative descriptive approach, data were gathered through in-depth interviews with public relations and media administrators, complemented by content analysis of both schools’ online channels. The findings show that MAN 1 Banjarmasin is more proficient in managing its website, offering structured, informative, and consistently updated content that boosts institutional credibility. In contrast, MAN 2 Banjarmasin leverages Instagram more actively as an interactive space to engage students, parents, and the broader community through visual storytelling and social interaction. Despite these strengths, both schools encounter challenges related to limited human resources, technical skills, and insufficient institutional backing. This study underscores the need for integrated digital marketing strategies and recommends that madrasas build stronger cross-platform coordination to solidify their online identity, enhance public trust, and increase student enrollment through sustained engagement on digital media.